TWO EXAMPLES OF ANALYTIC REPRESENTATION OF DISTRIBUTIONS - Rechkoski, Nikola; Rechkoski, Vasko (Matematichki Bilten, 2003)
In thus work we found which the distributions which analytic representation are the functions \(Γ(z)\) and \(ζ(z)\).